The efficacy of mifepristone combined with methotrexate for the treatment of ectopic pregnancy: a systematic review and meta-analysis*. (31st December 2022) - Su, Qiling; Feng, Huiyan; Tian, Tian; Liao, Xiaoqian; Li, Yunhui; Li, Xiaomao
Abstract: Objective: Systematically evaluate the clinical efficacy of mifepristone combined with methotrexate therapy for ectopic pregnancy (EP), analyze the experimental designs, put forward improvement ideas. Methods: RCTs of mifepristone combined with mifepristone for EP until January 2022 in six databases were searched. The primary outcome indicator was the cure rate. RevMan 5.4 was used to analyse and the online GRADEpro tool was used to assess the certainty of the evidence. Results: Twenty-five RCTs involved 2263 patients. The cure rate was higher in the investigational group (OR = 4.09, 95%CI: [3.20, 5.22]), time of vagina stopped bleeding (MD = −11.21, 95%CI: [−11.85, −10.57]) and time of abdominal pain disappeared (MD = −6.24, 95%CI: [−6.63, −5.86]) were shorter in the investigational group, β-HCG level (MD = −585.32, 95%CI: [−609.62, −561.03]) was lower and diameter of the mass (MD = −1.23, 95%CI: [−1.40, −106]) was smaller in the investigational group. The certainty of the evidence for most outcomes was moderate or high, and only one was low. Conclusions: The combination of mifepristone and methotrexate can improve the efficacy of ectopic pregnancy without amplifying the toxic side effects. Larger scale and better design of the randomized controlled trials are needed. KEY MESSAGES: In recent years, the increase in ectopic pregnancies and their impacts on female fertility makes physicians have to find an effective medical treatment as soon as possible that can avoid surgery. The mifepristone combined with methotrexate therapy for EP has better curative effects on improving the cure rate, lowering β-HCG level, reducing the mass, and alleviating symptoms of abdominal pain and bleeding, without amplifying the toxic side effects. Literature with high quality is lacking, and well-designed, large-scale and high-quality multicenter randomized controlled trials are needed.